Return on shares of steel companies under the influence of mergers and acquisitions - J. Zuzik; R. Weiss; E. Weiss; L. Mixtaj; A. Kiraly (Metalurgija, 2015)
The present article intends to asses returns on shares of the steel companies that were formed based on either merger or acquisition. The analysis included 14 operations in the steel industry. Attention was paid to returns of the companies performing acquisitions, as well as to the returns on shares that presented the acquisition target. The analysis was performed based on the “event study” method, and the analysed event was the announcement or notification of realization of an acquisition. Shares of the target steel companies as well as acquirers are attaining higher returns, but the change was not statistical significant.